(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
In this article, it is stated that the information provision of pedagogical education is very diverse and multidisciplinary, and in this regard, it is necessary to improve the quality of education using information-based educational methods that lead to high pedagogical efficiency in the most relevant, practically valuable and promising topics, and to create an information-educational environment from them. researches were conducted on issues of optimal use in the process of formation.